Reduced cerebral gray matter and altered white matter in boys with Duchenne muscular dystrophy - Doorenweerd, Nathalie; Straathof, Chiara S.; Dumas, Eve M.; Spitali, Pietro; Ginjaar, Ieke B.; Wokke, Beatrijs H.; Schrans, Debby G.; van den Bergen, Janneke C.; van Zwet, Erik W.; Webb, Andrew; van Buchem, Mark A.; Verschuuren, Jan J.; et al. (Annals of neurology, 2014)
Objective Duchenne muscular dystrophy (DMD) is characterized by progressive muscle weakness caused by DMD gene mutations leading to absence of the full‐length dystrophin protein in muscle. Multiple dystrophin isoforms are expressed in brain, but little is known about their function. DMD is associated with specific learning and behavioral disabilities that are more prominent in patients with mutations in the distal part of the DMD gene, predicted to affect expression of shorter protein isoforms. We used quantitative magnetic resonance (MR) imaging to study brain microstructure in DMD. Methods T1‐weighted and diffusion tensor images were obtained on a 3T MR scanner from 30 patients and 22 age‐matched controls (age = 8–18 years). All subjects underwent neuropsychological examination. Group comparisons on tissue volume and diffusion tensor imaging parameters were made between DMD patients and controls, and between 2 DMD subgroups that were classified according to predicted Dp140 isoform expression (DMD_Dp140+ and DMD_Dp140−). Results DMD patients had smaller total brain volume, smaller gray matter volume, lower white matter fractional anisotropy, and higher white matter mean and radial diffusivity than healthy controls. DMD patients also performed worse on neuropsychological examination. Subgroup analyses showed that DMD_Dp140− subjects contributed most to the gray matter volume differences and performed worse on information processing. Interpretation Both gray and white matter is affected in boys with DMD at a whole brain level. Differences between the DMD_Dp140− subgroup and controls indicate an important role for the Dp140 dystrophin isoform in cerebral development. Ann Neurol 2014;76:403–411